Multilocus phylogeography of the endemic and endangered angular angelshark (Squatina guggenheim) in the Southwest Atlantic Ocean - Bunholi, Ingrid Vasconcellos [UNESP]; da Silva Ferrette, Bruno Lopes; Domingues, Rodrigo Rodrigues; Rotundo, Matheus Marcos; Cuevas, Juan Martín; García, Mirta; Gómez, Sebastián; de Freitas, Renato Hajenius Aché; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP]; Mendonça, Fernando Fernandes (Springer Nature, 2022)
The angular angelshark (Squatina guggenheim) is a coastal endangered angel shark from the Southwest Atlantic Ocean and one of the major bycatch victims. Despite major concerns about this species, little is known about its evolutionary connectivity across its whole geographic distribution. Here, genetic connectivity and phylogeographic patterns of S. guggenheim for 122 individuals were assessed across the Southwest Atlantic Ocean regions based on a multilocus mitochondrial DNA approach to support conservation strategies. The concatenated mitochondrial dataset (control region, cytochrome b and cytochrome c oxidase I) showed high levels of haplotype diversity and low nucleotide diversity in S. guggenheim, with distinct genetic diversity patterns among populations. Although signs of stepping-stone gene flow were observed, a strong and statistically significant genetic structure into at least two populations was detected, matching with the species’ biological traits and region’s oceanographic particularities. Contrasting demographic patterns were detected, in which only southernmost Atlantic populations showed signs of population expansion. Despite the existence of connectivity among regions, our results suggest that conservation plans should be carried out following the uniqueness of each management unit.
Keywords: Conservation genetics; Elasmobranch; Genetic diversity; Mitochondrial DNA; Population structure; Southwest Atlantic